The Influence of Slippage on Trapping and Reflux Limits with Peristalsis through an Asymmetric Channel - Z. M. Gharsseldien; Kh. S. Mekheimer; A. S. Awad (Applied Bionics and Biomechanics)
The effects of slip boundary condition on peristaltic transport of incompressible Newtonian viscous fluid in an asymmetric channel is investigated, under the conditions of low Reynolds number and long wavelength. The pumping characteristics, trapping and reflux limits are studied for different values of the dimensionless slip parameter β.